Visualisasi Data dan Prediksi Perkembangan Impor Barang di Indonesia Tahun 2010 – 2014 - Billy Riadi; Johan Setiawan (Universitas Multimedia Nusantara, 2018)
Import is one of the trade process conducted between two countries, the import process is done by a country to meet the needs of the country that is not meet by the ability of the country. Indonesia also imports many items such as fuel or rice. Therefore, to reduce the level of imports, we need to know which sector has the most import rate and whether the level of imports in that sector is increasing or not, so Indonesia can save the country's foreign exchange reserves.Import data Indonesia displayed in the form of visualization of data created using the method of Visual Data Mining (VDM) and using Power BI as a tools. Indonesian Import Prediction is done to know the growth of Indonesia import rate by using Linear Regression method and using SPSS tools.In a study of the growth of import levels in Indonesia, Indonesia has an import rate that increased between 8-20%, but in some periods experienced an increase and decrease caused by other factors such as consumption expenditure, currency exchange rates and state revenues.